PENGARUH TEKNIK THINK TALK WRITE (TTW) BERBASIS MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS X SMAN 7 PADANG - Rahayu, Fania Sri; Basri, Irfani; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT This article is written to determine the effect TTW discovery techniques learning model based on the skills of writing text LHO of the students class X SMAN 7 Padang. Data of this study is the result of the test writing skills LHO text before and after treatment. Data collected by the performance test by providing employment to students in the form of LHO writing text test. LHO text writing skills before and after treatment compared to see the effect of model-based techniques TTW discovery learning by using t-test formula. The results showed that (1) the skills to write LHO text of the students class X SMAN 7 Padang before using the technique think talk write model-based discovery learning is in the Enough qualification, (2) the skill of LHO writing text after using the technique think talk write model-based discovery learning students class X SMAN 7 Padang are in Good qualification, (3) based on the t-test, concluded that there was a significant influence on the use of model-based techniques TTW discovery learning in teaching LHO writing text of the students class X SMAN 7 Padang. Kata kunci: pengaruh, teknik think talk write TTW berbasis model discovery                   learning, menulis teks laporan hasil observasi